A Managerial approach for Waste Management: A Case Study of Solid and Liquid Waste Management into Solid and Liquid Resource Management - Reddy.S, Vijayachandra; Ramachandran, Rema (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
The study focus on managing waste household resources such as Citric fruits peel, cattle non-edible items,cotton,coconut ,tender coconut shells, wood and twings,non-vegetarian waste, husk sponge, cattle edible leaves(garden waste) , Areca nut leaf plates,seeds,reaper leaf, food waste and other materials which are segregated into organic and inorganic materials which are classified into  two colored baskets per household where bio-degradable waste are placed in the green basket and non-biodegradable waste in the red basket respectively. Many Self-help Groups (SHG) are involved in this segregation process which is we call it as Primary source segregation of waste materials obtained from home shops, markets, households. This segregation helps to pool all the waste resources in useful organic material used in agriculture production process. At this point the question arise how much quantity can be managed by these SHG or any parties involved in waste management process. Because many research studies on especially municipal waste reveals that around 366 cities in India are accounted for 31.6 million tons of waste in the year 2001 where as now it has increased to grow around 47.3 million tons,  which reveals about 50 per cent growth in span of one decade. Now the challenge is how these wastes can be managed or these wastes can be dumped into oceans which act as new uncontrolled dumpsites. However, there are some islands creating unfavorable for aquatic habitat environmental growth. Hence to resolve these kind of problem, this study suggest the importance of Solid and Liquid Waste management (SLWM) into Solid and Liquid Resource management (SLRM) which is predominantly used and practiced as SLRM model in Kurudam palayam near Coimbatore and the Plastic waste burns to give cooking gas Model developed in NIT Calicut are major innovations used for household waste management into useful resource in production.